2014
DOI: 10.1016/j.nima.2014.06.083
|View full text |Cite
|
Sign up to set email alerts
|

The optimum choice of gate width for neutron coincidence counting

Abstract: In the measurement field of international nuclear safeguards, passive neutron coincidence counting is used to quantify the spontaneous fission rate of certain special nuclear materials. The shift register autocorrelation analysis method is the most commonly used approach. However, the Feynman-Y technique, which is more commonly applied in reactor noise analysis, provides an alternative means to extract the correlation information from a pulse train. In this work we consider how to select the optimum gate width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…In standard MSR electronics this expression corresponds to T g $ 1.27τ as shown in [1,10]. Extension of these considerations towards RTI approach was performed in [9], where it was shown that for purely random gates, this relationship is modified to T g $ 2.14τ. Wider optimum gate width setting is thus favored by the RTI analysis.…”
Section: Pu Assay and Related Operating Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In standard MSR electronics this expression corresponds to T g $ 1.27τ as shown in [1,10]. Extension of these considerations towards RTI approach was performed in [9], where it was shown that for purely random gates, this relationship is modified to T g $ 2.14τ. Wider optimum gate width setting is thus favored by the RTI analysis.…”
Section: Pu Assay and Related Operating Parametersmentioning
confidence: 99%
“…Graphical representation of relative standard deviation (RSD) versus coincidence gate width then exhibits a shallow minimum corresponding to the optimum gate width setting. This approach was applied in [9] to a series of 252 Cf sources to provide a comparison with the above theoretical estimates. It was shown that the optimum coincidence gate width varies strongly with the 252 Cf neutron emission rate with longer gates being favored for weaker sources, although it is common practice to use a universal coincidence gate width value for a given detector type.…”
Section: Pu Assay and Related Operating Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the method used for the analysis, various combinations of gate generators, delay lines, shift register coincidence circuits and variable dead time circuits [6,7,9,10] are used to acquire the data in the experiment. Work related to gate width optimisation and gate generation technique was reported recently [11,12]. Thus the configuration of electronics modules for acquisition of data is specific to the theoretical method used for the data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…system. Naturally, the measurement variance has been studied before, and there are several publications regarding both the estimation [1,6,7] and the optimization [8,9] of the measurement variance. The emphasis in previous works is mainly on analytic expressions for the random variance, and the bootstrap method (or any other re-sampling method) was somewhat neglected.…”
Section: Introductionmentioning
confidence: 99%